SISTEM MONITORING DAYA LISTRIK MENGGUNAKAN INTERNET OF THING (IOT) BERBASIS MOBILE - Doni Azizi; Veri Arinal (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) AMIK Indonesia, 2023)
This research aims to develop an electrical energy monitoring system using Internet of Things (IoT) technology and based on mobile applications to increase the efficiency of electrical energy use and reduce energy waste. The context of this research is the increasingly urgent need to monitor and optimize electrical energy consumption, both in domestic and industrial environments, as part of efforts to reduce environmental impact and Operating costs related to electricity consumption. The methodology used in this study includes the design and implementation of an IoT system consisting of energy sensors and hardware connected to the Internet, as well as the development of a mobile application as a user interface. Energy consumption data recorded by the sensors will be transmitted wirelessly to mobile applications for real-time monitoring and analysis. The results of this study show that an IoT-based electrical energy monitoring system is capable of providing accurate and timely information on electrical energy consumption, thereby helping users increase energy efficiency and Reduce operating costs related to electricity consumption. Additionally, the system allows users to easily monitor and control electrical energy consumption through their mobile devices, which in turn can contribute to more resilient and sustainable energy management. This research is important in efforts to create a more sustainable and energy-efficient environment, as well as raise public awareness about electrical energy consumption.